2010
DOI: 10.1186/1471-2334-10-109
|View full text |Cite
|
Sign up to set email alerts
|

Lives saved by Global Fund-supported HIV/AIDS, tuberculosis and malaria programs: estimation approach and results between 2003 and end-2007

Abstract: BackgroundSince 2003, the Global Fund has supported the scale-up of HIV/AIDS, tuberculosis and malaria control in low- and middle-income countries. This paper presents and discusses a methodology for estimating the lives saved through selected service deliveries reported to the Global Fund.MethodsGlobal Fund-supported programs reported, by end-2007, 1.4 million HIV-infected persons on antiretroviral treatment (ARV), 3.3 million new smear-positive tuberculosis cases detected in DOTS (directly observed TB treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 31 publications
1
40
1
Order By: Relevance
“…An earlier estimation using a similar methodology indicated that at the end of 2007, DOTS was responsible for 67% of all lives saved by Global Fund–supported programmes, while ART and ITNs contributed 28% and 5%, respectively [8]. However, these proportions will have changed due to the extensive scale-up of ITNs since 2008 leading to greater reductions in mortality due to malaria [9].…”
Section: The Global Fund's Estimate Of “Lives Saved”mentioning
confidence: 99%
“…An earlier estimation using a similar methodology indicated that at the end of 2007, DOTS was responsible for 67% of all lives saved by Global Fund–supported programmes, while ART and ITNs contributed 28% and 5%, respectively [8]. However, these proportions will have changed due to the extensive scale-up of ITNs since 2008 leading to greater reductions in mortality due to malaria [9].…”
Section: The Global Fund's Estimate Of “Lives Saved”mentioning
confidence: 99%
“…Examples include essential neonatal care, essential obstetric care, malaria case management, case management of severe malnutrition and management of the HIV infected child. Reported examples of successful scaling-up of such packages are usually drawn from large, internationally well-funded programmes in fields such as HIV 5. In contrast, support for widespread implementation of cross-cutting interventions such as WHO/UNICEF's Integrated Management of Childhood Illnesses can be half-hearted even if the approach is formally adopted at policy level 6 7…”
Section: Introductionmentioning
confidence: 99%
“…The survival assumptions follow those used by UNAIDS in their routine estimates on the global HIV epidemic 23. In addition to the GFATM annual reports, there has also been an impact assessment published as a journal article by Komatsu and colleagues 24. The methods used in the article differed only slightly from those used in the official GFATM reports.…”
Section: Two Shifts In the Delivery Of Hiv Treatment And Carementioning
confidence: 99%